Savage skies - Edwards, Cassie (New York Leisure Enfield Publishers Group UK [distributor], 2007)
When she is rescued by Chief Blue Thunder from rape and torture at the hands of the Comanche, Shirleen, on the run from her abusive husband and searching for her missing daughter, finds salvation in his powerful arms.
98835
Keywords: Indians of North America; Love stories; Historical fiction